Augmented reality in engineering education: Strategic design and evidence-based results - Sebastián Donaire; Rodrigo Barraza; Pedro Martínez-Pagán; Marcos A. Martínez-Segura; Luis Alvarez; Lorena Yepes-Bellver; Víctor Yepes (PLoS ONE, 2026)
The primary objective of this study is to define and empirically validate a novel procedural methodological framework, named SEBAS (Selection, Establishment, Blueprint, Application, Synthesis), for the strategic integration of Augmented Reality (AR) learning activities in higher engineering education. The research addresses the lack of specialized methodologies for using AR in the complex and technical discipline of mining engineering and evaluates the impact of the implementation on student educational outcomes. A mixed-method quasi-experimental design was employed, involving 136 undergraduate students enrolled in mining-related programs. A specific group of these students participated in augmented reality (AR) workshops developed using the SEBAS framework. Quantitative data on academic performance history were collected, along with qualitative data from pre- and post-intervention surveys to assess students’ perceptions and motivation. The results demonstrated a substantial positive impact on academic performance. Participating students achieved a higher average final grade (4.70, SD = 1.75) compared to the overall group (4.30, SD = 1.98). Welch’s t-tests confirmed statistically significant differences in the courses with higher AR integration (Course 1, t(36)=3.30, p = 0.002; Course 2, t(38)=10.03, p < 0.001). A thorough qualitative analysis was conducted, which yielded substantial evidence of a considerable positive shift in student perceptions, levels of interest, and practical applicability. The primary contribution of this research is the SEBAS framework, which offers a structured, pedagogically sound, and replicable model for incorporating immersive technologies. This framework facilitates the development of strategically designed AR activities that enhance academic performance, promote cognitive engagement, and prepare students for the challenges of the industry.